Support, Facilities And Services For Ageing Academic Staff At Two Indonesian Public Universities - Ramadhan, Adityo Pratikno (2023)
This research aims to analyse the ageing policy in two fully autonomous Indonesian public universities employing a sequential exploratory mixed method as a research method.